Late-onset severe neutropenia in patients with relapsing remitting multiple sclerosis treated with ocrelizumab: case report and literature review - Tauro, Catherine; Awada, Zeinab; Malhotra, Radhika; Harel, Asaff (Frontiers in Neuroscience, 2025)
ObjectiveTo describe two cases of recurrent, delayed-onset severe neutropenia several months following ocrelizumab therapy in patients with relapsing–remitting multiple sclerosis (RRMS).BackgroundA rare adverse effect of ocrelizumab is neutropenia, with late-onset neutropenia (LON) occurring more rarely. Literature guiding management of transient recurrent neutropenia in the setting of anti-CD20 therapy is lacking.MethodsCase 1: 38-year-old female emergency physician with RRMS developed severe transient spontaneously resolving asymptomatic neutropenia 3 months after ocrelizumab infusion. Two years later, she developed severe symptomatic LON and required antibiotics and granulocyte colony-stimulating factor (GCSF). Ocrelizumab was held, patient switched to ozanimod, but neutropenia recurred. Due to concerns of MS progression, ocrelizumab was restarted after the patient transitioned to a telehealth setting, with no recurrence of neutropenia at one-year follow-up. Case 2: 35-year-old male emergency physician with RRMS developed severe transient spontaneously resolving asymptomatic neutropenia 3 months after ocrelizumab infusion. Ocrelizumab was resumed after absolute neutrophil count recovery. Two years later, he developed moderate symptomatic LON during a suspected viral illness. Ocrevus was discontinued at this point. A subsequent episode occurred 3 months later during confirmed rhinovirus infection, again resolving promptly.ConclusionThese cases highlight the unpredictable nature of recurrent LON with ocrelizumab and suggest the possibility of immune-mediated marrow suppression, potentially unmasked or worsened by infections, rather than direct drug toxicity, highlighting the need for clearer management guidelines.